Residual compressive strength of polyamide fiber‐reinforced epoxy composites after low‐velocity impact. Issue 5 (2nd February 2023) - Coskun, Taner; Yar, Adem; Demir, Okan; Sahin, Omer Sinan
Abstract: In this study, polyamide fibers, which stand out with their excellent plastic deformation and energy absorption capacity, were used as reinforcement materials, and in‐house manufactured composite specimens were subjected to low‐velocity impact (LVI), compression after impact (CAI) and tensile tests. Within this scope, one and two repeated drop tests were performed under 3 m/s velocity to determine LVI responses and how impact number affects the dynamic properties. CAI tests were also performed at a 1 mm/min crosshead speed, and mechanical properties for non‐impacted, one‐impacted, and two‐impacted specimens were determined. As a result of the outstanding plastic deformation capacity of thermoplastic fabrics, it is concluded that polyamide composites exhibited quite large strains. Furthermore, it was understood from the tensile responses that tensile stresses were carried by the thermoplastic fibers in two different regimes and significantly high toughness was obtained. Moreover, reductions in the maximum compression loads, critical buckling loads and axial stiffness were observed due to degradation in structural integrity after impact loads. Additionally, the utilization of recyclable thermoplastic polyamide fibers as reinforcement material instead of conventional reinforcement materials such as carbon and glass fibers provide more environmentally friendly products. Abstract :